Plant life history and above–belowground interactions: missing links - Deyn, Gerlinde B. De (Oikos, 2017)
The importance of above–belowground interactions for plant growth and community dynamics became clear in the last decades, whereas the numerous studies on plant life history improved our knowledge on eco-evolutionary dynamics. However, surprisingly few studies have linked both research fields despite their potential to increase our mechanistic understanding of how above–belowground interactions are governed. Here I briefly review studies on above–belowground interactions and plant life history and identify important research gaps. To advance our understanding of ecological strategies and eco-evolutionary dynamics of plants and their associated organisms it is warranted to elucidate the interconnectivity and tradeoffs of plant life history traits of growth, defence, reproduction, nutrient cycling and the functional composition of above- and belowground heterotrophic communities. Using the concept of tradeoffs in growth, reproduction and defence we can postulate that plants in rich soil grow, reproduce and die fast whilst avoiding above- and belowground antagonists, whereas plants in poor soil grow slow, live and reproduce longer and invest in above- and belowground mutualists and defences. However, alternative scenarios are possible and depend on the selection pressure by above- and belowground mutualists and antagonists during plant ontogeny and via after-life effects. To elucidate missing links between life history traits and above–belowground interactions, complementary modelling and empirical studies are needed that reveal the coupling between below- and aboveground plant traits of growth, defence and reproduction, their heritability and their cost/ benefit relation. These cost/benefit analyses of defence should span from individuals to future generations, taking feedback effects via altered biotic communities and resource competition into account. The role of soil fertility in steering plant life history traits requires explicit testing of trans-generational trait shifts in growth, defence, reproduction, cost/benefit of associations with mutualists and antagonists and soil feedbacks across plant genotypes/species with distinct life history traits, grown across soil fertility gradients.